Keeping Ethical Investment Ethical: Regulatory Issues for Investing for Sustainability - Richardson, Benjamin J. (Journal of business ethics, 2009)
Regulation must target the financial sector, which often funds and profits from environmentally unsustainable development. In an era of global financial markets, the financial sector has a crucial impact on the state of the environment. The long-standing movement for ethically and socially responsible investment (SRI) has recently begun to advocate environmental standards for financiers. While this movement is gaining more adherents, it has increasingly justified responsible financing as a path to be prosperous, rather than virtuous. This trend partly owes to how financial institutions view their legal responsibilities. The business case motivations that now predominantly drive SRI are not sufficient to make the financial sector a means to sustainable development. Some modest legal reforms to improve the quality and extent of SRI have yet to make a tangible difference. A more ambitious strategy to promote SRI for environmental sustainability is possible, based on reforming the fiduciary duties of financial institutions. Such duties, tied to concrete performance standards, could make financiers invest in more ethically responsible ways. Other collateral reforms to financial markets, including improved corporate environmental reporting, are required to promote sustainability.